Changes in calcium accumulation and utilization efficiency and their impact on recycling, immobilization, and export across the oil palm cycle - Viégas, Ismael de Jesus Matos; Souza, Luma Castro de; Ferreira, Eric Victor de Oliveira; Costa, Milton Garcia [UNESP]; Nogueira, Glauco André dos Santos; Nascimento, Vitor Resende do; Oliveira Neto, Cândido Ferreira de (Elsevier, 2024)
Effective calcium (Ca) management is crucial for optimizing oil palm cultivation and enhancing crop yield. This study aimed to gain insights into the dynamics of Ca concentration, accumulation, exportation, immobilization, and recycling in various oil palm organs relative to plant age. The experiment was conducted at the Agropalma enterprise site in the northeastern region of Pará State, Brazil, evaluating seven plant age treatments: 2, 3, 4, 5, 6, 7, and 8 years old. Employing a completely randomized design with four replications. The results demonstrated an age-related increase in Ca concentration in petioles, rachis, arrows, male inflorescences, peduncles, and fruits. Furthermore, Ca accumulation exhibited an upward trend in all organs with progressing plant age. Notably, the study revealed an enhanced Ca use efficiency across all plant organs in correlation with the age of oil palm cultivation. These findings underscore the dynamic nutritional demands of oil palm, influencing Ca immobilization, cycling, and export throughout its developmental stages.
Keywords: Amazon; Ca cycling; Ca export; Ca immobilization; Ca use efficiency; Elaeis guineensis Jacq.; Plant nutrition